2011
DOI: 10.1590/s0100-83582011000500022
|View full text |Cite
|
Sign up to set email alerts
|

Potential of macrophytes for removing atrazine from aqueous solution

Abstract: -The potential of three macrophytes, Azolla caroliniana, Salvinia minima, and Lemna gibba was assessed in this study to select plants for use in environmental remediation contaminated with atrazine. Experiments were carried out in a greenhouse over six days in pots containing Hoagland 0.25 strength nutritive solution at the following atrazine concentrations: 0; 0.01; 0.1; 1.0; 10.0 mg L -1 . Decrease in biomass accumulation was observed in the three macrophytes, as well as toxic effects evidenced by the sympto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…caroliniana plants have the capacity to remove atrazine from the environment with an accumulation of ca. 0.018 mg per fresh mass gram when the plants are exposed at 10.0 mg·L –1 ATZ concentration . These authors also report that A.…”
Section: Results and Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…caroliniana plants have the capacity to remove atrazine from the environment with an accumulation of ca. 0.018 mg per fresh mass gram when the plants are exposed at 10.0 mg·L –1 ATZ concentration . These authors also report that A.…”
Section: Results and Discussionmentioning
confidence: 69%
“…0.018 mg per fresh mass gram when the plants are exposed at 10.0 mg•L −1 ATZ concentration. 52 These authors also report that A. caroliniana biomass was not reduced by ATZ at <1.0 mg•L −1 levels, indicating a good tolerance of the plant to the herbicide. On the other hand, for the higher dose of MP-ATZ (0.04 μmol•L −1 ), our results showed that values were statistically similar to ATZ, suggesting an early trend to improve the herbicidal effect on PSII that may be related to a time-/dose-dependent response of A. caroliniana plants and differences of the mechanism of action between the ATZ and MPs:ATZ.…”
Section: Determination Of Herbicide Encapsulationmentioning
confidence: 88%
“…The maintenance of a clear-water state by submerged macrophytes helps improve water quality in relation to eutrophication, but macrophytes benefits for water quality goes beyond this aspect. The concentrations of several inorganic and organic pollutants, including trace metals, atrazine, pharmaceuticals, pesticides and nanoparticles (Srivastava et al, 2008;Dhote & Dixit, 2009;Guimara ˜es et al, 2011;Kochi et al, 2020;Dias et al, 2021), only to cite some examples, reduce in the presence of macrophytes. The mechanisms explaining this ESs are beyond the scope of this review, but they are related to direct (e.g., absorption) and indirect (e.g., changes in the environment features, providing habitat for bacteria etc.)…”
Section: Regulating Servicesmentioning
confidence: 99%
“…Phytoremediation has been extensively implemented for treating pesticides in wetlands systems using different helophyte species (i.e., emergent plants) (Matamoros et al 2012;Vymazal and Březinová 2015;Vryzas 2016). Yet, an alternative approach based on aquatic free-floating plants can be utilized for agrochemical remediation or biomonitoring in water bodies (Guimarães et al 2011;Della Vechia et al 2016;Escolá Casas and Matamoros 2022). In this context, two subsets of phytoremediation are particularly promising for alleviating the water contamination by crop protection products: rhizodegradation and phytodegradation.…”
Section: Introductionmentioning
confidence: 99%